DNA damage and adverse neurological outcomes among garlic farmers exposed to organophosphate pesticides - Ratana Sapbamrer (2019)
© 2019 Elsevier B.V. Garlic farmers used organophosphate pesticides to control insects, resulting in an increased risk for adverse health outcomes. Thus, we investigated exposure to organophosphate pesticides, DNA damage, nerve conduction, and neurological symptoms among 134 garlic farmers. They were interviewed, measured nerve conduction, and collected blood and urine for determining DNA damage and dialkylphosphate metabolites. Total dialkylphosphate levels of farmers who began cultivating garlic in October were significantly higher than those of non-farmers and the farmers who began cultivating in November and December. Farmers showed significantly longer comet tail lengths and tail moments than non-farmers. However, their mean compound motor and sensory nerve action potential amplitudes of the median, ulnar, and common peroneal nerves were within normal ranges. Measurement of DNA damage is useful as a biomarker of long-term and low-level exposure to organophosphate pesticides; however, electromyography might be not sufficiently sensitive to detect nerve conduction effects in farmers exposed to pesticides.